PET/CT and contrast-enhanced CT imaging findings in benign solitary schwannomas - Wang, Si-yun; Liu, Jian-hua; Yao, Su; Wang, Shu-xia; Shao, Dan (European journal of radiology, 2021)
Imaging features of positron emission tomography (PET)/computed tomography (CT) and contrast-enhanced CT and pathological changes in benign solitary schwannoma were retrospectively analyzed, and the factors associated with high uptake of fluorodeoxyglucose (FDG) were examined. The PET/CT, contrast-enhanced CT, and pathological results of 58 cases of benign solitary schwannomas confirmed by surgery or biopsy were retrospectively analyzed. The association of each variable with the maximum standardized uptake value (SUVmax) was evaluated. The SUVmax of the 58 benign schwannoma cases was 4.1 ± 2.1 (1.5–11.1). When the locations of schwannomas were divided into gastrointestinal system/heart/abdominal and pelvic cavities/thoracic wall (type-1 locations) and other sites (type-2 locations), the schwannoma location was significantly correlated with the SUVmax (r = 0.538, p =  0.000). The SUVmax values were 5.8 ± 2.4 and 3.3 ± 1.5, respectively (p =  0.000). Peritumoral lymphoid cuffs were observed in 7 cases, 4 of which were tumors of gastrointestinal origin, accounting for 80 % of the gastrointestinal schwannomas (4/5). The presence of peritumoral lymphoid cuffs was significantly correlated with the SUVmax (r = 0.456, p =  0.000). The location of the schwannoma was significantly correlated with the presence of peritumoral lymphoid cuffs (r = 0.640, p =  0.000). We found that a peritumoral lymphoid cuff is strongly correlated with the presence of regional lymphadenopathy. Among the 7 cases showing peritumoral lymphoid cuffs, 5 cases had the presence of peritumoral enlarged lymph nodes. The degree of enhancement was significantly correlated with the SUVmax (r = 0.556, p =  0.000). Benign schwannomas originating from the gastrointestinal system/heart/abdominal location and showing the presence of peritumoral lymphoid cuffs or moderate and significant enhancement on contrast-enhanced CT were significantly associated with high FDG uptake. An accurate understanding of the factors associated with high FDG uptake can help reduce the misdiagnosis rate.